2021
DOI: 10.26508/lsa.202101162
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between MPIase, YidC, and PMF during Sec-independent insertion of membrane proteins

Abstract: Integral membrane proteins with the N-out topology are inserted into membranes usually in YidC- and PMF-dependent manners. The molecular basis of the various dependencies on insertion factors is not fully understood. A model protein, Pf3-Lep, is inserted independently of both YidC and PMF, whereas the V15D mutant requires both YidC and PMF in vivo. We analyzed the mechanisms that determine the insertion factor dependency in vitro. Glycolipid MPIase was required for insertion of both proteins because MPIase dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
(68 reference statements)
4
15
0
Order By: Relevance
“…MPIase was required for insertion of both substrates. In the case of Pf3-Lep, the dependency on YidC/ PMF increased with increasing substrate level, whereas V15D insertion was promoted by YidC/PMF regardless of the substrate level (Endo et al, 2022). These results indicate that the number of negative charges on the N-terminal side and the substrate level strongly affect the dependency on YidC and PMF.…”
Section: Interaction Between Membrane Protein Integrase and Yidcmentioning
confidence: 80%
See 1 more Smart Citation
“…MPIase was required for insertion of both substrates. In the case of Pf3-Lep, the dependency on YidC/ PMF increased with increasing substrate level, whereas V15D insertion was promoted by YidC/PMF regardless of the substrate level (Endo et al, 2022). These results indicate that the number of negative charges on the N-terminal side and the substrate level strongly affect the dependency on YidC and PMF.…”
Section: Interaction Between Membrane Protein Integrase and Yidcmentioning
confidence: 80%
“…The interplay of MPIase with YidC and PMF in the Secindependent pathway has also been analyzed using different substrates (Endo et al, 2022). In vivo experiments have shown that Pf3-Lep, an N-out type substrate, requires neither YidC nor PMF for membrane insertion, while its mutant, V15D, with increased N-terminal negative charges requires both YidC and PMF (Zhu et al, 2013).…”
Section: Interaction Between Membrane Protein Integrase and Yidcmentioning
confidence: 99%
“…Our recent study revealed that the protein released from the ribosome is captured by sugar chains of MPIase and attracted to the membrane surface through the pyrophosphate group 18 . In the presence of MPIase, some hydrophobic proteins such as the 3L-Pf3 coat, a mutant version of bacteriophage Pf3 coat protein, are inserted into the membrane without YidC, while YidC accelerates the insertion in combination with MPIase 19 , 20 . Therefore, we speculated that the hydrophobic region of the protein would be inserted into the membrane and the hydrophilic region would be delivered into YidC after attraction by MPIase.…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have demonstrated that YidC is fundamental for the addition of small phage coat proteins like Pf3 coat and M13 in a Sec-free pathway. 9,[26][27][28][29][30][31] A few experimental studies have explored the role of YidC in various microbial creatures. The genomes of most gram-positive microscopic organisms encode two YidC proteins:…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have demonstrated that YidC is fundamental for the addition of small phage coat proteins like Pf3 coat and M13 in a Sec-free pathway. 9,2631…”
Section: Introductionmentioning
confidence: 99%